CHC for pelvic pain in women with endometriosis: ineffectiveness or discontinuation due to side-effects. Issue 2 (28th February 2020) - Yong, Paul J; Alsowayan, Najla; Noga, Heather; Williams, Christina; Allaire, Catherine; Lisonkova, Sarka; Bedaiwy, Mohamed A
Abstract: STUDY QUESTION: What are the use patterns and factors associated with combined hormonal contraception (CHC) ineffectiveness or discontinuation due to side-effects in patients with endometriosis and pelvic pain? SUMMARY ANSWER: Worse chronic pelvic pain (CPP) severity and pelvic floor myalgia were associated with continuous CHC ineffectiveness, while poorer quality-of-life was associated with continuous CHC discontinuation due to side-effects. WHAT IS KNOWN ALREADY: CHC is a first line of therapy for endometriosis-associated pelvic pain in women. However, some patients state that CHC is ineffective for their pain, while others have to discontinue CHC due to side-effects. STUDY DESIGN, SIZE, DURATION: Analysis of a prospective patient database from a tertiary care referral center for patients with endometriosis and pelvic pain between December 2013 and April 2015 was carried out. PARTICIPANTS/MATERIALS, SETTING AND METHODS: A total of 373 patients of reproductive age with endometriosis from the database were included in the study. Data included patient self-reported questionnaires, physical examination findings and validated instruments. There were four variables of interest: history of cyclical CHC ineffectiveness (yes/no), history of cyclical CHC discontinuation due to side-effects (yes/no), history of continuous CHC ineffectiveness (yes/no) and history of continuous CHC discontinuation due to side-effects (yes/no). The primary outcome was CPP severity for the past 3 months (score of 0–10), and secondary outcomes were other pelvic pain scores, quality-of-life on the Endometriosis Health Profile 30 (EHP-30) and underlying conditions including irritable bowel syndrome, painful bladder syndrome, abdominal wall pain, pelvic floor myalgia and depression, anxiety and pain catastrophizing. MAIN RESULTS AND THE ROLE OF CHANCE: Among the 373 cases in the dataset, prior cyclical CHC use was reported by 228 (61.1%) women, of which 103 (27.6%) stated it was ineffective for their pain and 94 (25.2%) stated they discontinued CHC due to side-effects. Previous continuous CHC use was reported by 175 (46.9%) women, of which 67 (18.0%) stated it was ineffective and 59 (15.8%) stated they discontinued due to side-effects. Worse CPP severity in the last 3 months was associated with a history of continuous CHC ineffectiveness ( P  < 0.001). Poorer quality-of-life was present in women who reported a history of continuous CHC discontinuation due to side-effects ( P  = 0.005). Among the underlying conditions, pelvic floor tenderness (as a marker of pelvic floor myalgia) was associated with CHC ineffectiveness. LIMITATIONS AND REASONS FOR CAUTION: This study involved patient recall and no longitudinal follow-up. Also, we do not have data on the type of side-effect that led to discontinuation. Medication ineffectiveness was reported subjectively by the patient rather than using standardized criteria. Finally, the diagnosis of endometriosis was based on previous surgery or a current nodule or endometrioma on examination/ultrasound; without prospective surgical data on all the patients, it was not possible to do a sub-analysis by current surgical features (e.g. stage). WIDER IMPLICATIONS OF THE FINDINGS: In women with endometriosis, CHC ineffectiveness was associated with worse CPP and pelvic floor myalgia, which suggests myofascial or nervous system contributors to CPP that does not respond to hormonal suppression. A tender pelvic floor, as a sign of pelvic floor myalgia, may be a clinical marker of patients with endometriosis who are less likely to have an optimal response to hormonal suppression. For women who discontinue CHC due to side-effects, research is needed to help alleviate these side-effects as these patients report worse quality-of-life. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by a Canadian Institutes of Health Research (CIHR) Transitional Open Operating Grant (MOP-142273) as well as BC Women's Hospital and the Women's Health Research Institute. PY is also supported by a Health Professional Investigator Award from the Michael Smith Foundation for Health Research. MB/CA has financial affiliations with Abbvie and Allergan; the other authors have no conflicts of interest.